Application of seismic reflection survey for aquifer layers characterization at the Felda Lepar Utara area, Pahang, Malaysia - Ahmad Dedi Putra; Norasiah Sulaiman; Norsyafina Roslan; Habibah Jamil; Umar Hamzah; Khairunnisa Alias (Penerbit Universiti Kebangsaan Malaysia, 2022)
Precise determination of subsurface structure is crucial in hydrogeological studies to correctly determine the potential of groundwater resources, and the sustainability of those resources. This study used the seismic reflection method to characterize the aquifer layer in Ladang Lepar Utara 8 (Line 1) and Ladang Sungai Rengai (Line 2) in the Felda Lepar Utara area, Pahang, Malaysia, due to its high accuracy, high-resolution and deeper penetration. The field data acquisition survey involved roll-along techniques with shot spacing of 5m along the line using 24-channels ABEM terraloc Mark-6 and CMP (common mid-point) profiling techniques. Seismic interpretation of reflection data and tubewell information from nearby borehole data indicates that the area consists of a single type of rock known as phyllitic meta-sedimentary rocks of the Seri Jaya beds that have been deformed by intense faulting and fracturing (from about 30 to 750 m depth in Line 1 and about 75 m to 500m depth in Line 2). This formation is overlain by recent alluvium that ranges in thickness from 30 to 75 m and is underlain by Lepar Granodiorite. The alluvium is a shallow aquifer system that can be classified as an unconfined aquifer, whereas the phyllitic meta-sedimentary rock of the Seri Jaya Beds is a deep aquifer system that can be classified as a confined aquifer with an alluvium layer (up to 75 m thick) on top as a confining bed. The occurrence of intense faulting and fracturing increases the porosity and permeability of the rock formation and hence increases its potential as a groundwater prospective/promising zone.